Mining candidate genes for rice cadmium accumulation in the shoot through a genome-wide association study and transcriptomic analysis - Wang, Jian; Yang, Wu; Zhang, Shaohong; Dong, Jingfang; Yang, Tifeng; Ma, Yamei; Zhou, Lian; Chen, Jiansong; Liu, Bin; Zhao, Junliang (Frontiers in Genetics, 2022)
High Cadmium (Cd) accumulation in rice is a serious threat to human health. The genetic mechanism of Cd accumulation in rice is great complicated. To identify the low Cd accumulation rice germplasm, investigate the genetic mechanism underlying Cd accumulation and mine the elite genes of significant importance for rice breeding of low Cd accumulation varieties. We performed genome-wide association study (GWAS) for rice Cd concentration in shoot. The rice accessions were 315 diverse Indica rice accessions selected from the 1568 rice accessions with 700,000 SNPs. Within the high rate of linkage disequilibrium (LD) decay, 8 QTLs related to rice Cd accumulation were identified. Transcriptomic analysis showed there were 799 differentially expressed genes (DEGs) in root and 857 DEGs in shoot which are probably to be the cause of significant difference in Cd accumulation between high and low Cd accumulation varieties. In the qCd11-1, we detected a crucial candidate gene, LOC_Os11g11050, which encodes an initiation factor, expressed differently in root between the high and low Cd accumulation varieties. Furthermore, under Cd treatment, the expression levels of LOC_Os11g11050 significantly decreased in both the high and low Cd accumulation varieties. Sequence comparison and qRT-PCR revealed that there were indel sequences and base substitutions in the promoter region of LOC_Os11g11050 correlated to LOC_Os11g11050 expression level, as well as the phenotype of Cd concentration differences in shoot between the high and low Cd accumulation accessions. LOC_Os11g11050 might play important roles in Cd accumulation. The results of our study provide valuable resources for low Cd indica, and the candidate functional gene, as well as molecular mechanisms for Cd accumulation in indica rice. The genetic architecture underlying Cd accumulation in indica can be used for further applying the low Cd gene existing in Indica for improvement of Cd accumulation in rice.